Structural isomerism and effect of fluorination on gas adsorption in copper-tetrazolate based metal organic frameworks - Pachfule, Pradip; Chen, Yifei; Sahoo, Subash Chandra; Jiang, Jianwen; Banerjee, Rahul (Chemistry of Materials, 2011)
Synthesis, structure, and gas adsorption properties of three Metal Organic Frameworks (MOFs) synthesized from predesigned ligands 4-(1H-tetrazole-5-yl)benzoic acid (4-TBA) and 2-fluoro-4-(1H-tetrazole-5-yl)benzoic acid (2F-4-TBA) along with Cu(II) as an metal precursor has been reported. Among these MOFs, Cu-9(4-TBA)(10)(C2H5OH)(2) (Cu-TBA-1) and Cu-2(4-TBA)(2)(DMF)(C2H5OH) (Cu-TBA-2) are structural isomers. Whereas, Cu-2(4-TBA)(2)(DMF)(C2H5OH) (Cu-TBA-2) and Cu-2(2-F-4-TBA)(2)(DMF)(2) (Cu-TBA-2F) have similar crystal structure. N-2 adsorption isotherms of the activated sample of Cu-TBA-1 and -2 exhibit types-I sorption behavior with a Langmuir and Brunauer-Emmett-Teller (BET) surface area of 686, 402 m(2)/g and 616, 356 m(2)/g, respectively. It is noteworthy that Cu-TBA-1 and -2 adsorbs 1.16 and, 1.54 wt % H-2, while Cu-TBA-2F adsorbs 0.67 wt % at 77 K and 1 atm. On the other hand, Cu-TBA-1 and -2 adsorb 3.08 and 2.54 mmol/g, while Cu-TBA-2F adsorbs 1.27 mmol/g of CO2 at 298 K and 1 bar pressure. H-2 adsorption sites in Cu-TBA-2 and -2F have been analyzed by molecular simulation.
Keywords: CO2 adsorption; fluorination; Hydrogen storage; Metal-organic framework; structural isomerism

Solid-state thermolysis of anion induced metal-organic frameworks to ZnO microparticles with predefined morphologies: facile synthesis and solar cell studies - Kundu, Tanay; Sahoo, Subash Chandra; Banerjee, Rahul (Crystal Growth & Design, 2012)
Simple one-step solid state thermolysis of two Zn-based homochiral metal organic frameworks (MOFs) leads to a dramatic difference in morphologies which depends on the anion (-Cl and -Br) and calcination environment (air and N-2). Rod-shaped (aspect ratio similar to 20), hexagonal column shaped (aspect ratio similar to 3), and elliptical aggregation of ZnO morphologies (aspect ratio similar to 3) are obtained and characterized. Although these two MOFs possess similar rod-shaped morphology, they produce dramatic change in resulting ZnO microparticle morphologies (from rod-shaped ZnO microparticles in the case of thermolysis of MOP 1 to hexagonal column shaped ZnO microparticles in the case of MOF 2 thermolysis) when calcined in N-2 at 800 degrees C. However, when we calcined both MOF 1 and 2 in air, we encountered similar elliptical aggregation of ZnO microparticles. These ZnO microparticles show permanent porosity, visible light emission centered at 605 or 510 nm. Moreover, they show 0.15% and 0.14% dye sensitized solar cell activity. To the best of our knowledge, this is the first report of dye sensitized solar cell activity of ZnO microparticles obtained from one-step thermolysis of porous homochiral MOFs.

Salt metathesis in three dimensional metal-organic frameworks (MOFs) with unprecedented hydrolytic regenerability - Kundu, Tanay; Sahoo, Subash Chandra; Saha, Subhadeep; Banerjee, Rahul (Chemical Communications, 2013)
{Eight Zn-based porous (1.2 nm) homochiral MOFs (ValZnX, AlaZnX